Comprehensive analysis of epigenetics mechanisms in osteoporosis - Chen, Yuzhu; Sun, Yumiao; Xue, Xiangyu; Ma, Huanzhi (Frontiers in Genetics, 2023)
Epigenetic modification pertains to the alteration of genetic-expression, which could be transferred to the next generations, without any alteration in the fundamental DNA sequence. Epigenetic modification could include various processes such as DNA methylation, histone alteration, non-coding RNAs (ncRNAs), and chromatin adjustment are among its primary operations. Osteoporosis is a metabolic disorder that bones become more fragile due to the decrease in mineral density, which could result in a higher risk of fracturing. Recently, as the investigation of the causal pathology of osteoporosis has been progressed, remarkable improvement has been made in epigenetic research. Recent literatures have illustrated that epigenetics is estimated to be one of the most contributing factors to the emergence and progression of osteoporosis. This dissertation primarily focuses on indicating the research progresses of epigenetic mechanisms and also the regulation of bone metabolism and the pathogenesis of osteoporosis in light of the significance of epigenetic mechanisms. In addition, it aims to provide new intelligence for the treatment of diseases related to bone metabolism.